Elevated phospholipase D isoform 1 in Alzheimer's disease patients' hippocampus: Relevance to synaptic dysfunction and memory deficits. Issue 1 (15th February 2018) - Krishnan, Balaji; Kayed, Rakez; Taglialatela, Giulio
Abstract: Introduction: Phospholipase D (PLD), a lipolytic enzyme that breaks down membrane phospholipids, is also involved in signaling mechanisms downstream of seven transmembrane receptors. Abnormally elevated levels of PLD activity are well‐established in Alzheimer's disease (AD), implicating the two isoforms of mammalian phosphatidylcholine cleaving PLD (PC‐PLD1 and PC‐PLD2). Therefore, we took a systematic approach of investigating isoform‐specific expression in human synaptosomes and further investigated the possibility of therapeutic intervention using preclinical studies. Methods: Synaptosomal Western blot analyses on the postmortem human hippocampus, temporal cortex, and frontal cortex of AD patient brains/age‐matched controls and the 3XTg‐AD mice hippocampus (mouse model with overexpression of human amyloid precursor protein, presenilin‐1 gene, and microtubule‐associated protein tau causing neuropathology progressing comparable to that in human AD patients) were used to detect the levels of neuronal PLD1 expression. Mouse hippocampal long‐term potentiation of PLD1‐dependent changes was studied using pharmacological approaches in ex vivo slice preparations from wild‐type and transgenic mouse models. Finally, PLD1‐dependent changes in novel object recognition memory were assessed following PLD1 inhibition. Results: We observed elevated synaptosomal PLD1 in the hippocampus/temporal cortex from postmortem tissues of AD patients compared to age‐matched controls and age‐dependent hippocampal PLD1 increases in 3XTg‐AD mice. PLD1 inhibition blocked effects of oligomeric amyloid β or toxic oligomeric tau species on high‐frequency stimulation long‐term potentiation and novel object recognition deficits in wild‐type mice. Finally, PLD1 inhibition blocked long‐term potentiation deficits normally observed in aging 3XTg‐AD mice. Discussion: Using human studies, we propose a novel role for PLD1‐dependent signaling as a critical mechanism underlying oligomer‐driven synaptic dysfunction and consequent memory disruption in AD. We, further, provide the first set of preclinical studies toward future therapeutics targeting PLD1 in slowing down/stopping the progression of AD‐related memory deficits as a complementary approach to immunoscavenging clinical trials that are currently in progress.